A Laser Heater Undulator for FLASH2020+. Issue 1 (1st December 2022) - Telawane, S; Schöps, A; Neumann, P; Ramm, T; Tischer, M; Vagin, P
Abstract: Space charge induced micro bunch instabilities, amplified in cascaded bunch compression stages, spoil the phase space of compressed bunches and lead to unstable seeding. To "heat" up the bunch with an external laser and induce an uncorrelated energy spread to suppresses the micro bunching instabilities, a short undulator will be installed in front of the first compression chicane. The undulator has a planar hybrid magnet structure with 43 mm period length, 11 full periods, 22 mm minimum gap and a deflection parameter K of 1.52 (K = (eBλ u / (2 πme c, with B - max. magnetic field amplitude, λ u - period length) to match the 534 nm laser wavelength at 146 MeV beam energy. The paper describes the undulator's compact design, its control system and results of magnetic measurements and tuning.